Assessment of Calcium Carbide Waste and Calcined Clay as Stabilizer in Flexible Pavement Construction - Quadri, H. A.; Abiola, O. S.; Odunfa, S. O.; Azeez, J. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Stabilization techniques have often been used globally to enhance properties of weak subgrade materials for flexible pavement construction. This study assessed the blend of calcium carbide waste (CCW) and calcined clay (CC) to serve as an effective stabilizer of Subgrade material (S) sourced from a section along Ota-Idiroko road. Subgrade material was initially modified with CCW in different percentage replacements by weight (0, 4, 8, 12, 16 and 20%) and the resulting blends were subjected to Atterberg’s limits test to determine the blend with optimum plasticity index reduction which would be tagged optimum subgrade lime blend (OSLB). The blend of S + 8% CCW was tagged OSLB because it exhibited optimum plasticity index reduction. The OSLB was thereafter blended by weight with CC in the following percentage replacements 3, 6, 9, 12, 15 and 18% in order to activate the pozzolanic potentials of CC for strength enhancement. The resulting blends were subjected to Atterberg’s limits, Compaction, California bearing ratio (CBR) and Unconfined compressive strength (UCS) tests with the strength specimens cured for 0, 3, 7, 28, 56 and 90 days. The results showed that OSLB-CC blends reduced the Plasticity index from14.8 to 8.4 %, Maximum dry density from 1.82 to 1.54 Mg/m3, Optimum moisture content, 23.7 to 17.9 % and increased soaked CBR, 0 to 418.2% and UCS, 201.59 to 5660.84 kPa of natural subgrade respectively. Furthermore, the blends showed great improvement with reduction in PI less than standard value of 10% and increment in standard CBR and UCS values of 180% and 1700 kPa respectively for base course material. Therefore, stabilized blends at 7 days curing period could improve the natural subgrade to subbase and base for pavement construction.